Os tuberculóides reacionais - Opromolla, Diltor Vladimir Araujo (1994)
Twenty patients with generalized type I reaction and positive Mitsuda test equal 6 mm or more, were studied. Clinic, baciloscopic, histopathologic and evolutionaries features were considered. Erythematous lesions, papules and plaques, with well defined edges, and little involvement of nerves were observed in all cases. Bacillary index was negative or very low and the histopathologic findings included loose tuberculoid granuloma due to intracellular and intercellular edema and vascular congestion. Very few patients presented more than one acute episode. The authors suggested that the eruption is due to bacillary multiplication. The reactional flare would be a kind of delayed hypersensitivity to the antigens released during the destruction of bacilli. They claim that these cases exist and need to be recognized for a better understanding of the disease and this fact may have therapeutics implications since they present many lesions with few or no bacilli, and a trend to spontaneous cure.